2007
DOI: 10.1080/08860220601184134
|View full text |Cite
|
Sign up to set email alerts
|

A Fatal Case of Paraquat Poisoning Following Minimal Dermal Exposure

Abstract: Paraquat is a pesticide widely used in agriculture. Numerous cases of paraquat intoxication have been reported either accidentally or intentionally as a suicidal attempt. The most severe cases of paraquat poisoning refer to oral ingestion. Complications include respiratory, hepatic, and renal failure, and are usually fatal. Dermal exposure is less frequent and rarely fatal.This article reports a case of an 81-year-old man with minimal skin burn after accidental paraquat exposure. The patient developed acute re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(31 citation statements)
references
References 20 publications
0
29
0
2
Order By: Relevance
“…A case report described skin burns resulting from minimal accidental paraquat exposure, which subsequently lead to acute renal and respiratory failure and ultimately death. 74 Another report described prolonged dermal paraquat exposure as a result of a crop-dusting accident, also resulting in death. 85 Epidemiology studies have also associated self-reported paraquat usage with Parkinson's disease, most likely because of the increased production of reactive oxygen species resulting from the toxicity of the herbicide.…”
Section: Agriculture and Forestrymentioning
confidence: 99%
“…A case report described skin burns resulting from minimal accidental paraquat exposure, which subsequently lead to acute renal and respiratory failure and ultimately death. 74 Another report described prolonged dermal paraquat exposure as a result of a crop-dusting accident, also resulting in death. 85 Epidemiology studies have also associated self-reported paraquat usage with Parkinson's disease, most likely because of the increased production of reactive oxygen species resulting from the toxicity of the herbicide.…”
Section: Agriculture and Forestrymentioning
confidence: 99%
“…Paraquat dichloride (1,1′-dimethyl-4,4′-bipyridinium dichloride, methyl viologen dichloride hydrate, PQ) is a quaternary nitrogen herbicide that has been extensively used all over the world since the middle of the 20th century. Its inherent high toxicity to plants is also extended to humans resulting in both chronic exposure and intentional/accidental acute toxicity, frequently reported as fatal (Almog and Tal, 1967;Hsu et al, 2003;Russell et al, 1981;Soloukides et al, 2007). The lung is known to be the target organ for PQ's cytotoxicity (Dinis-Oliveira et al, 2006a), although the liver and the kidneys may also be affected.…”
Section: Introductionmentioning
confidence: 99%
“…Urinary paraquat concentrations of <1 mg/L within 24 hours of toxicity have a high probability of survival. [567] Since patient reported to us after 13 days of ingestion, data regarding serum and urine levels at specific time points is lacking. We did not confirm the presence of paraquat by using dithionite test in urine or plasma.…”
Section: Discussionmentioning
confidence: 99%